Mechanical Behaviour and Impact of Various Fibres Embedded with Eggshell Powder Epoxy Resin Biocomposite - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Natural fiber composites are becoming an alternate material to synthetic fiber composites, and the use of eggshell bio-filler has been explored in polymer composites as environmental protection. Jute, coir, and sisal fibers were utilized in this research to make composites out of natural fibers. Polymer composites were made using epoxy resin with different amounts of eggshell powder (ESP) as fillers (2%, 4%, 6%, 8%, and 10% of weight). The mechanical and biodegradability properties of the synthesized composites were investigated. The testing results showed that composites with an optimum percentage of 6% ESP as filler improved mechanical characteristics significantly in all three fiber composites. Among the three fibers, coir fiber with 6% ESP added showed a substantial increase in tensile, flexural, impact, and hardness strength properties by 34.64%, 48.50%, 33.33%, and 35.03%, respectively. In addition, the percentage weight loss of coir fiber composites at 9 weeks is noteworthy in terms of biodegradability testing. As a result, epoxy composites containing eggshell fillers could be employed in applications requiring better tensile, flexural, impact, and hardness strength. © 2022 by the authors.